Increasing the values of the state defense among youth in fighting the threat of radicalism - Tommy Mandala Putra; I Wayan Midhio; Deni D.A.R. (Universitas Pertahanan Republik Indonesia (UNHAN RI), 2022)
State defense awareness is the right and obligation of every citizen. Observing Article 27 Paragraph (3) and Article 30 Paragraph (1), it implies that efforts to defend the state in defending state are the rights and obligations of every citizen without exception. In terms of defending the country, youth need to improve their understanding of the values of defending the country so that they can ward off the threat of radicalism that continues to occur. Youth in the future will experience various threats, such as the threat of radicalism to terrorism. So, to overcome the existing threat, increasing the values of defending the country for youth is the right step in maintaining youth nationalism and patriotism as a form of love for the homeland. Improvement can be implemented through the method of defending the country and the design of materials that are relevant to the psychological characteristics of young people. Overcoming youth dislocation and social deprivation through social inclusion programs. And planting religious insight (religiosity) that is integrated with national insight.